Influence of Pt-Sn System Nanostructure on the Electronic Conditions at a Pt Adsorption Surface Site - Bortoloti, Francielle [UNESP]; Ishiki, Nicolas A. [UNESP]; Della-Costa, Maria-Laura F. [UNESP]; Rocha, Kleper O. [UNESP]; Angelo, Antonio C. D. [UNESP] (Amer Chemical Soc, 2018)
This paper describes the synthesis and full characterization of Pt-Sn intermetallics with the same stoichiometry and similar particle size but distinct atomic arrangements (ordered intermetallic, ordinary alloy, and core-shell configuration). We propose that these distinct structures provide different electronic conditions to the noble metal's surface adsorption site, which could influence the active catalytic species's electrochemical potential. We prepared ordered intermetallic PtSn, ordinary PtSn alloy, and Sn@PtSn core-shell structures by three different methods. X-ray diffraction (XRD) confirmed the chemical identity of the products, and energy-dispersive X-ray spectrometry attested to a 1:1 Pt/Sn atomic ratio for all the materials. High-resolution transmission electron microscopy showed that the mean particle size ranged from 2 to 3 nm for the ordered intermetallic and alloy structures and was about 4 nm for the core-shell material. Electron diffraction corroborated the chemical identity of the materials that was earlier suggested by the XRD measurements and evidenced the ordered intermetallic character of the shell in Sn@PtSn. In conclusion, the X-ray absorption technique with synchrotron radiation demonstrated that the different Pt-Sn structures afforded distinct electronic conditions for the same Pt surface adsorption site, probably due to changes in the energy of the bond established between Pt and Sn in the investigated materials. The results obtained here will guide the development of (electro)catalysts and will aid understanding of (electro)catalytic processes for various purposes.